DETERMINAN PERTUMBUHAN EKONOMI DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2007-2014 DETERMINANTS OF ECONOMIC GROWTH IN SPECIAL REGION OF YOGYAKARTA PERIOD 2007-2014 - Wiwin Ratnasari (EKPI IE 16 UMY 025, 2016)
*25 This research aims at tasting the Determinants of Economic Growth. The populations becoming the object of the research are the Districts/Municipalities of the Special Region of Yogyakarta. The data availability is in accordance with the research period that is providing the data of Labor from 2007 to 2014, the average length of study from 2007 to 2014, and the Real Per Capita Expenditure Data which is adjusted with the purchasing power obtained from the Central Bureau of Statistics. The analysis model used is the panel data regression test, the result obtained is that the Labor, Average Length of Study, and the Real Per Capita Expenditure which is adjusted with the Purchasing Power have Positive and Significant toward the Economic Growth Keywords: Economic Growth, Labor, Average Length of Study, and Real Per Capita Expenditure which is adjusted with the Purchasing Power.